Efek kredibilitas dan kemenarikan selebgram dalam mempengaruhi niat beli konsumen - Setyawan, Didik; Noliana, Maria Sanggita Putri; Yulandari, Ariefah (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2021)
The phenomenon that occurs in celeb-grams in the media that have millions of followers is not all effective enough in influencing the attitude of their followers to buy a brand. This study aims to examine the effect of credibility and attractiveness of a celebrity in changing consumer attitudes to intend to make a purchase. This study uses the Elaboration Likelihood Model as the basic model, which is modified for its application to social media. This study uses an experimental design method for hypothesis testing through 2 stages of testing, namely study 1 and study 2, with participants being social media users who know about Scarlett Whitening products but have never made a purchase. The results show that high source credibility and attractiveness can increase consumers' positive attitudes to influence purchase intention rather than low source credibility and attractiveness.